The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3171/2014.10.peds14107
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of resective epilepsy surgery after invasive presurgical evaluation in children with tuberous sclerosis complex and bilateral multiple lesions

Abstract: OBJECT Tuberous sclerosis complex (TSC) with medically refractory epilepsy is characterized by multifocal brain abnormalities, traditionally indicating poor surgical candidacy. This single-center, retrospective study appraised seizurerelated, neuropsychological, and other outcomes of resective surgery in TSC patients with medically refractory epilepsy, and analyzed predictors for these outcomes. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 16 publications
7
55
2
2
Order By: Relevance
“…The recent EXIST 3 study showing higher efficacy of adjunctive everolimus therapy in patients with treatment-refractory seizures associated with TSC compared to placebo, is promising in this regard. 30,31 This might be the main limiting factor for epilepsy surgery but should be a reminder to refer patients with pharmacoresistant epilepsy early on to expert epilepsy surgery centers to define the possibility of such therapy that is showing fair results, even in patients with multiple foci. 23 There has been substantial progress in understanding of diagnosis and treatment of epilepsy in patients with TSC during the last decade.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent EXIST 3 study showing higher efficacy of adjunctive everolimus therapy in patients with treatment-refractory seizures associated with TSC compared to placebo, is promising in this regard. 30,31 This might be the main limiting factor for epilepsy surgery but should be a reminder to refer patients with pharmacoresistant epilepsy early on to expert epilepsy surgery centers to define the possibility of such therapy that is showing fair results, even in patients with multiple foci. 23 There has been substantial progress in understanding of diagnosis and treatment of epilepsy in patients with TSC during the last decade.…”
mentioning
confidence: 99%
“…Epilepsy surgery for patients with TSC needs specific expertise, as there is often more than a single tuber focus and surgery may need invasive monitoring of seizures to determine the resection area. 30,31 This might be the main limiting factor for epilepsy surgery but should be a reminder to refer patients with pharmacoresistant epilepsy early on to expert epilepsy surgery centers to define the possibility of such therapy that is showing fair results, even in patients with multiple foci. 32 The correlation between intellectual ability and seizure control in TSC has been reported.…”
mentioning
confidence: 99%
“…After epilepsy surgery, authors have reported rates of seizure freedom (Engel Class I outcome) between 48 and 84% depending on the follow-up interval (Arya et al, 2015;Fallah et al, 2015;Liang et al, 2017;Weiner, 2006;Zhang et al, 2013). An extensive presurgical evaluation is carried out and each patient is discussed at a multidisciplinary conference to determine surgical candidacy.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…An extensive presurgical evaluation is carried out and each patient is discussed at a multidisciplinary conference to determine surgical candidacy. After epilepsy surgery, authors have reported rates of seizure freedom (Engel Class I outcome) between 48 and 84% depending on the follow-up interval (Arya et al, 2015;Fallah et al, 2015;Liang et al, 2017;Weiner, 2006;Zhang et al, 2013). Positive predictors of seizure freedom after surgery include younger age at seizure onset, greater extent of resection, focal EEG abnormalities, EEG and MRI concordance, and the absence of generalized seizures or significant developmental delay (Fallah et al, 2013;Fallah et al, 2015;Zhang et al, 2013).…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Previous studies in TSC showed that an aggressive, often multilobar resection can render children with a large or multifocal epileptogenic zone seizure-free in a substantial number of cases. 23,24 In children with a larger epileptogenic zoneoften with multilesional or nonlesional MRI-interictal spike populations may represent irritative zones that are distinct from or only barely overlapping with the SOZ. This is the principle behind the decision to perform IEM even when there are frequent ECoG abnormalities.…”
Section: Clinical Implications Of Ecog Abnormalitiesmentioning
confidence: 99%